The perception of colombians about science and technology according to their education level: professional and non-professional population - Carolina Delgado-Hurtado; Carlos Augusto Osorio-Marulanda; Carlos Felipe Rengifo-Rodas; Jaime Mosquera-Restrepo (Revista Facultad de Ingeniería Universidad de Antioquia, 2016)
This document discusses the results of the implementation of the ThirdNational Survey on Public Perception of Science and Technology applied in Colombia. Itanalyzes the effect of education over some aspects related to the perception about Scienceand Technology of the Colombians, considering variables such as age and professionalizationof the population. Methodologically, the research type is quantitative and descriptive;it uses statistical tools like frequency tables, histograms and subsampling techniques toavoid a biased comparison of the populations. The major findings presented are that thelevel of education acquired and the formal training actually have significance regardingthe perceptions about science and technology in the studied population; it proved to affectthe perception and attitude towards issues as the preference in the choice of a career fordaughters and sons, the tendency for reviewing instructions and exploring the use of theinformation, the perception of whether the country works on science or not, and if peoplemake science and technology. In the future, it will be required an approach based ondifferential studies, addressing the impact of the dissemination of science and technology.